“The external imprint of our self”. Notes on the first features of the right to one’s own image: Peer reviewed article (Italian Review of Legal History, 2021)
The paper addresses the “very modern” right to one’s own image, in the unfolding of its dynamics through the kaleidoscopic and crucial Nineteenth-Twentieth century turning. Attention is paid in particular to legal scholarship and case law, which have helped to outline and then define an autonomous subjective right having as its object one’s personal image, and to find for it a systematization within the legal order, from the end of the Nineteenth century to publication of the First Book of the Civil Code. Technical innovation in progress raises the issue, as the reproduction and wide spread of the human physiognomy, facilitated by the potentialities of modern devices and means of communication, sharpens the urgency of protection for what appears to be both strictly inherent to the person and related to the social projection of the individual. From the defense of honor and reputation, to protection from undue intrusions into the personal sphere, the complex issue is at the crossroads of different legal areas and opens in the Twentieth century to unexpected developments and transformations. In fact, it gradually fits into a more complex conception of the person, which emerges from a scientific reflection transversal to the fields of sociology, anthropology, philosophy, biology, and turns in the direction of ‘personal identity’.
Keywords: Right to One’s Own Image; Civil Codification; Rights related to Personality; Personal Identity Right; Copyright; European Legal History; Contemporary History